KORELASI SENSITISASI ALERGEN INDOOR DENGAN FREKUENSI EKSASERBASI ASMA PADA ANAK - , Irene; , dr. Putu Siadi Purniti, Sp.A ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The rapid increase in asthma incidence implies to the importance of environmental factor over genetic factor. Sensitisation to perennial indoor allergens has been associated with the increase of asthma symptoms. This research aims to identify the correlation between sensitisation to indoor allergens and asthma severity in children. A cross-sectional study was held in the Pediatric Department of Sanglah Hospital, Denpasar, on asthmatic children aged 6 to 12 years. The degree of sensitisation was assessed by the mean wheal diameter (positive â¥ 3 mm from negative control) for seven common indoor allergens. Frequency of asthma exacerbation for three consecutive months prior to data collection was retrospectively reviewed. Skin test results from 84 of 89 (94%) asthmatic children were positive for one or more allergens. The median of patientsâ ages was 93 months (interquartile range 81-117 months), and males constituted 64%. Higher frequency of asthma exacerbation was significantly correlated with the numbers of allergens with positive sensitisation (r=0,284